Legal Analysis of Land Sale And Purchase Deeds Made Not in Accordance With the Provisions of Government Regulation Number 24 of 2016 (Case Study of Supreme Court Decision Number 3507 K/PDT/2023) - Florentina Cristy; Mia Hadiati (Journal of Law, Politic and Humanities, 2024)
This research aims to examine the validity of the deed made by the Deed Official. The State of Indonesia declares itself as a State of law which means that all aspects of life including all activities, regulations, and decisions to be taken by the Government must be based on all applicable laws in the State of Indonesia. The leadership system adopted by Indonesia is a Presidential government where the President is given the duty and trust as the Head of State. In exercising his governmental powers, the President is assisted by state ministers appointed and dismissed by the President. Regarding the scope of Land Registration in Indonesia, the Government is assisted by the National Land Agency and the Land Deed Official. The presence and role of the Land Deed Official in ensuring legal certainty of land status and ownership is very important because it is the main pillar, the condition for the authenticity of a deed, as proof that a legal action has occurred regarding land rights. In carrying out his position, the Land Deed Official is obliged to comply with statutory regulations, namely Government Regulation Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning Regulations on the Position of Land Deed Officials.  The presence and role of the Land Deed Official in ensuring legal certainty of land status and ownership is very important because it is the main pillar, the condition for the authenticity of a deed, as proof that a legal action has occurred regarding land rights. In carrying out his position, the Land Deed Official is obliged to comply with statutory regulations, namely Government Regulation Number 24 of 2016 concerning Amendments to Government Regulation Number 37 of 1998 concerning Regulations on the Position of Land Deed Officials. This research, namely by examining the Supreme Court Decision Number 3507 K / Pdt / 2023, and the statutory approach to understanding how the law is applied in the concrete situation of the case.